Ekspansi Perkebunan Pisang Melalui Modal Ventura Serta Meningkatkan Efisiensi Operasi - Amir Farid; Kin Tjendrasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Indonesia, renowned for its fertile terrain, has great potential for fruit plantation due to its land and market. Bananas, especially the globally favored Cavendish variety, are predominant in both production and consumption. In this dynamic market, PT Sewu Segar Nusantara (Sunpride) stands as the dominant entity, leaving other players, like PT Lampung Banana Agri, with minimal market traction. PT Lampung Banana Agri is one of the players in the industry struggling to compete due to limitation of resources and operational challenges. Over the past five years, the company has encountered negative income, and signaling an urgent need for strategic redirection to maintain operational viability. This research ventures into understanding these challenges, deriving insights from both internal and external vantages. Employing tools like SWOT, VRIO, and financial ratio analysis, the company's intrinsic strengths and weaknesses are spotlighted. At the same time, frameworks like PESTLE and Porter's Five Forces clarify the macroeconomic and market forces at play. Central to this exploration is an analysis of the company's financial statements from 2016-2022, with a caveat: the reliance on public data means certain assumptions might need real-world validation. From these comprehensive analysis, actionable strategies emerge. The TOWS Matrix, an essential analytical tool, bridges internal capabilities with external opportunities, leading to concrete recommendations. A prime proposition is the acceleration of PT Lampung Banana Agri's production and sales, aiming for a swift return to profitability. Capital budgeting methodologies further validate the viability of farm expansion, identifying venture capital as a potential financial ally. It is noteworthy that even with the heftier interest rates inherent to venture capital, the benefits to the company are pronounced. Sensitivity analysis further underscore the pivotal role of product pricing, demonstrating its precedence over interest rate considerations. In essence, this research offers PT Lampung Banana Agri a roadmap, potentially transforming challenges into opportunities within Indonesia's competitive banana market. Keywords: Cavendish, Net Present Value (NPV), Financial Ratios, Capital Budgeting